Pendekatan Taktis dalam Pembelajaran Passing Atas pada Permainan Bolavoli - Hambali, Sumbara (Prodi PGSD Penjas FPOK UPI, 2018)
The purposive of study to improve the results of learning passing up on the game bolavoli by using a play approach. Research subjects were all students of class V SDN Sukasirna amounted to 24 people. Research method using action research with Kemmis and Taggart design. The results obtained on the pre cycle average student score of 65.35 with students who have not completed as much as 58.3%, while the completed as much as 41.7%. In the first cycle the average student score increased to 69.55 with the unfinished student as much as 29.1%, while the completed 70.9%. And on the second cycle average student score increased to 76.27 with students who have not completed as much as 16.7%, while that has been completed as much as 83.3%. Based on these results it can be concluded that by using the approach to play the results of learning passing up on the game bolavoli increased. That way the physical education teacher can use the play approach in his teaching process.Â Keywords: Learning Outcomes, Top Passing , Approach to Play